Media, Practice and Theory Tracking emergent thresholds of experience - Brabandere, Nicole De; Brabandere, Nicole De (Vernon Press, 2023)
This volume gathers research at the intersection of art and the interdisciplinary humanities to develop an understanding of media assemblages that insist on the generativity of their situatedness within ecologies of practice. These contributions propose media assemblages that enlarge the time and space for co-compositions between media and bodies that reshape subjective, perceptual, and affective registers of experience. Media assemblages include photography, performance, criticism, curation, installation, animation, collage, video and VR, as well as archival and somatic practices. Research as a form of practice is a key orientation in this volume since it offers a means of engaging the world-making proposition offered by Isabelle Stengers that practices are specified through irreducible entanglements that cause one to think, feel, and hesitate. The generative linkages between different disciplinary approaches for engaging research practice across the arts and humanities are favoured over disciplinary and media-based exclusivity. When practice is not posed as an intervention or counterpoint to scholarly research or in opposition to the discursive, differences emerge, not based on convention but through the situatedness of emergent insight. The goal is thus not to forward a reproducible formula for knowledge creation but to weave the conditions for utterances both within and in excess of discipline, convention, and establishment. How can research engender the making of communities between, across, and in excess of institutional frameworks through the emergent affinities, postures, and formats of evolving and inclusive forms of research? This volume is a valuable reference for researchers/practitioners within the arts and humanities as it exemplifies both critical and situated methods for developing interdisciplinary research as a means of transforming the terms of research itself.